Preventive Maintenance Planning Using Age Replacement Method for Head Router Machines: Perencanaan Pemeliharaan Preventif Menggunakan Metode Penggantian Berdasarkan Usia untuk Mesin Router Kepala - Eka Anestya Octavia; Rusindiyanto Rusindiyanto (Academia Open, 2025)
General Background: In the current industrial era, uninterrupted machine performance is crucial to minimize production losses. Specific Background: At PT BMN Pasuruan, the Head Router machine frequently experiences unplanned downtime, particularly in its bearing and spindle components. Knowledge Gap: While corrective maintenance has been applied, there is limited research on systematic preventive maintenance planning for these components using quantitative reliability models. Aims: This study applies the Age Replacement method to determine optimal replacement times and inspection intervals for the bearing and spindle, with the goal of reducing unplanned downtime. Results: Findings reveal that the optimal replacement time is 59,240 minutes for the bearing and 70,740 minutes for the spindle, with recommended inspection intervals of 340 hours (15 days) and 280 hours (12 days), respectively. Implementation of this strategy reduces downtime by 78.57% for the bearing and 77.69% for the spindle. Novelty: The research demonstrates the practical application of Age Replacement in a real industrial setting, offering measurable improvements in operational efficiency. Implications: Beyond solving PT BMN Pasuruan’s specific challenges, the study provides a transferable model for other manufacturing industries dependent on precision equipment. Highlights: Optimized replacement times minimize unexpected machine failures. Inspection intervals significantly reduce downtime. Age Replacement method improves industrial efficiency. Keywords: Preventive Maintenance, Age Replacement, Downtime Reduction, Spindle, Bearing